Transaksi Jual Beli Produk Impor Telematika dan Elektronika dalam Perspektif Undang - Putu Wilang Pra Yoga; I Nyoman Sujana; Ida Ayu Putu Widiati (Jurnal Interpretasi Hukum, 2021)
The amount of import of telematics and electronic products which will be marketed in the country do not qualify, then the need for legislation to protect consumer interests. In this research, a focus on the legal protection of trade-related consumer telematics and electronic products imported by Law - Act No. 8 of 1999 on Consumer Protection utilizing formulation of the problem is I. How will the buying and selling of imported telematics and electronic products in Indonesia? 2. How is the legaJ protection for consumers in buying and selling transactions of imported telematic and electronic products in the event of default. The research objective is to know about buying and selling arrangements related to the import of telematics and electronic products in Indonesia and to be useful for people, especiaJly consumers. The method used is normative legaJ research. The research result of trade-related settings telematics and electronic products imported regulated in the Trade Minister Regulation No. 38 of 2019. Following the protection of consumers, businesses that harm consumers by deliberately being subject to Article 60 are subject to administrative sanctions.